Considerations Regarding a New Settlement Typology in Serbia - Pantić, Marijana (Arhitektura i urbanizam, 2021)
A division between urban and rural settlements/areas has been traditionally applied in statistical reporting worldwide. The reports applying these terms have been used to create and implement development policies and measures. However, international policies such as those featured by the European Union (EU), as well as national policies, also recognize, define and render transitional types of settlements. The Program of Implementation of the Spatial Plan of the Republic of Serbia (2010) called for a new definition of the term “settlement” determined by new criteria for a settlement typology by the end of 2015. Except for theoretical contributions, this task has not been completed yet. At the same time, a trichotomous settlement typology has been recommended to Serbia by the EU as a result of the accession process. Therefore, this paper aims to analyze and discuss a new settlement categorization, taking into account considerations on the number of categories, number of variables, choice of variables and territorial level for data collection. These aspects are empirically tested on a data set collected through the Survey on Income and Living Conditions (SILC) in Serbia. The data are analyzed using two approaches: descriptive and cluster analysis. A parallel with other countries and theoretical recommendations is drawn in the discussion, based on which some recommendations are presented.
Keywords: settlement typology; Survey on Income and Living Conditions (SILC); cluster analysis; Serbia